Time to think beyond door to balloon time: significance of total ischemic time in STEMI - Sanam Khowaja; Salik Ahmed; Rajesh Kumar; Jehangir Ali Shah; Kamran Ahmed Khan; Naveed Ullah Khan; Tahir Saghir; Syed Nadeem Hasan Rizvi; Nadeem Qamar; Musa Karim (The Egyptian Heart Journal, 2021)
Abstract Background Significance of total ischemic time (TIT) in the context of ST-segment elevation myocardial infarction (STEMI) is still controversial. Therefore, in this study, we have evaluate the association of TIT with immediate outcomes in STEMI patients in whom recommended door to balloon (DTB) time of less than 90 min was achieved. Results A total of 5730 patients were included in this study, out of which 80.9% were male and median age was 55 [61–48] years. The median DTB was observed to be 60 [75–45] min and onset of chest pain to emergency room (ER) arrival time was 180 [300–120] min. Prolonged TIT was associated with poor pre-procedure thrombolysis in myocardial infarction (TIMI) flow grade (p = 0.022), number of diseased vessels (p = 0.002), use of intra-aortic balloon pump (p = 0.003), and in-hospital mortality (p = 0.002). Mortality rate was 4.5%, 5.7%, and 7.8% for the patients with TIT of ≤ 120 min, 121 to 240 min, and > 240 min, respectively. Thirty days’ risk of mortality on TIMI score was 4.97 ± 7.09%, 5.01 ± 6.99%, and 7.12 ± 8.64% for the patients with TIT of ≤ 120 min, 121 to 240 min, and > 240 min, respectively. Conclusions Prolonged total ischemic was associated with higher in-hospital mortality. Therefore, TIT can also be considered in the matrix of focus, along with DTB time and other clinical determinants to improve the survival from STEMI.